Tożsamość osobowa w świetle motywów akwatycznych w twórczości Wasyla Stusa - Liubych, Alina (Slavia Orientalis, 2025)
This article is devoted to the issue of personal identity considered through the prism of aquatic motifs as manifest in the work of the most outstanding Ukrainian poet of the second half of the 20th century, Vasyl Stus. Drawing on various critical perspectives and biographical facts about Stus himself, this article shows how water motifs reflect the complexity and formation of personal identity. Through an interdisciplinary analysis spanning cultural studies, history, psychology and philosophy, the issue of identity is described and compared to fluidity, transformation, and sometimes ephemerality. Moreover, the article explains how the exploration of personal identity, through the significance of water motifs, intersects with traditional views of society, rooted in cultural consciousness and historical events.